The challenges coped by the novice in nursing practice - Silva, Denise Guerreiro Vieira da; Souza, Sabrina da Silva de; Trentini, Mercedes; Bonetti, Albertina; Mattosinho, Mariza Maria Serafim (Revista da Escola de Enfermagem da USP, 2010)
The purpose of the study was to investigate the challenges faced by the nurses during the first years of their nursing work. A total of 31 novice nurses were included in the sample that answered a questionnaire with open and closed questions. The data analysis was conducted by using the qualitative software called Atlas Ti. The novice nurses deal with some challenges related to: a) leadership team; b) the competence and technique ability. The findings suggested that the nursing novice is not well prepared for assuming a leadership role as well as for caring in the settings of high-complexity. In order to cope those challenges new strategies of education and nursing practice has to be developed together with nurses educators and nurses practitioners.